2021
DOI: 10.4081/aiua.2021.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction and testosterone levels prior to COVID-19 disease: What is the relationship?

Abstract: Objective: We aimed to investigate the relationship between COVID-19 and Erectile Dysfunction (ED) and the effect of serum testosterone level on the disease prognosis. Methods: Between April-December 2020, 70 patients who were admitted with a complaint of ED after having COVID-19 and whose serum testosterone level was checked for varicocele, premature ejaculation, and infertility reasons before COVID-19. The patients filled the International Index of Erectile Function (IIEF-5) and their testosterone level was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
4
0
3
Order By: Relevance
“…The results of this study represented that the levels of testosterone of patients before and after COVID-19 were significantly different. They also concluded that high testosterone levels increase the rate of hospitalization in the intensive care unit by intensifying the disease [17].…”
Section: Sex and Gender Aspects In Covid-19mentioning
confidence: 99%
“…The results of this study represented that the levels of testosterone of patients before and after COVID-19 were significantly different. They also concluded that high testosterone levels increase the rate of hospitalization in the intensive care unit by intensifying the disease [17].…”
Section: Sex and Gender Aspects In Covid-19mentioning
confidence: 99%
“…Karkin and Alma also revealed changes in endothelium, in corpus cavernosum biopsy, in patients who had developed COVID-19 [ 30 ]. Also, the testosterone level was significantly lower after COVID-19 infection [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports describing increased risk of ED after COVID-19 have been limited to small cohort studies (<75 COVID-positive men), but have shown reduction of International Index Erectile Function-5 (IIEF-5) scores after COVID-19 infection and increased rates of ED compared to age-matched controls [10,12,13]. Evaluation of corporal tissue months after COVID-19 infection revealed persistence of COVID-19 peplomers suggesting a possible pathophysiologic mechanism for ED [7].…”
Section: Introductionmentioning
confidence: 98%